Detection of Mefenamic Acid in Hyperuricemia Herbal Medicine using UV-Vis Spectrophotometry and FTIR Spectroscopy Combined with Chemometrics - Putri, Anggita Rosiana; Kalima, Nanda; Ihsan, Bachtiar Rifai Pratita; Hardaniani, Prisma Trida (Journal of Food and Pharmaceutical Sciences, 2025)
The adulteration of herbal medicines with synthetic drugs poses a serious risk to public health. Mefenamic acid, a non-steroidal anti-inflammatory drug (NSAID), is sometimes illicitly added to herbal products marketed for hyperuricemia to enhance their therapeutic effect. This study aims to detect the presence of mefenamic acid in herbal medicines for hyperuricemia using a combination of UV-Vis spectrophotometry and Fourier Transform Infrared (FTIR) spectroscopy coupled with chemometric. approaches, specifically Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) and Partial Least Squares (PLS). The UV-Vis method was validated and showed good linearity with an R² value of 0.999. Accuracy testing revealed recovery rates ranging from 98.75% to 101.92%, while precision testing produced %RSD values between 0.86% and 1.05%. The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.235 ppm and 0.711 ppm, respectively. FTIR spectral data were processed using OPLS-DA and PLS to classify and predict adulterated samples. The validated OPLS-DA model demonstrated strong classification performance, effectively distinguishing between adulterated and non-adulterated samples. Furthermore, the detection results from UV-Vis, OPLS-DA, and PLS methods were consistent, confirming the reliability of the integrated approach.